Solvent optimization in moringa leaves' flavonoids extraction using simplex lattice design - Siti Muhsonah Oktaviana; Wahida Hajrin; Nisa Isneni Hanifa (Acta Pharmaciae Indonesia : Acta Pharm Indo, 2022)
Background: Flavonoids found mainly as pharmacologically active natural ingredient of moringa (Moringa oleifera L.). Therefore, optimizing the solvent to maximize the levels of flavonoid components is needed. Objective: This study was conducted to determine the optimum solvent composition for extracting flavonoid compounds from moringa leaves using the simplex lattice design (SLD). Methods: Moringa leaves were extracted using the sonication method with five combinations of 96% ethanol and water as the solvent. The solvent composition was optimized using Design-Expert version 11 software. Moreover, UV-Vis spectrophotometry was used to screen and identify flavonoid content. Results: Flavonoids were detected in moringa extract. Using the F test, a valid SLD equation, y= 440,243(A) + 142,983(B) - 47,324(A)(B), was obtained. This equation shows that the solvent ethanol 96% : water (100:0) was the best solvent and produced the maximum amount of moringa flavonoid content, which was 440,2427 mg QE/g extract. Conclusion: The flavonoid content was directly proportional to the high composition of 96% ethanol.